Web-Based Patient Management System / Nur Munirah Mohd Rozaiman - Mohd Rozaiman, Nur Munirah (2017)
Web-based Patient Management System (WBPMS) is a research and development project for the development of a patient management system for Klinik Kesihatan Merlimau (KKM). This web based system aims in helping in managing KKM’s patients’ registration and health record. Furthermore, it also helps in setting up and managing patients’ future appointments with their respective health provider. The main drive for this project is that KKM still uses traditional file-based system that reduce the efficiency of the staffs working there due to time consumption of searching of the records, other than possible of data redundancy. There are a few methodologies that had been compared in order to guide this project. And one of it had been chosen, that is waterfall methodology due to its suitability with the environment of the developer had been working in and the nature of this project area. This methodology consists of five phases but had been reduced to four due to time constraint. Those phases that was included here is project planning, analysis, design and implementation. Documents such as System Requirement Specification (SRS) and System Design Document (SDD) were produce together with this report to explain more on the results of needs and requirements’ analysis and the design based on the analysis that had been made. WBPMS had been successfully developed as a result of this project.